The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11154-022-09730-z
|View full text |Cite
|
Sign up to set email alerts
|

Androgens, aging, and prostate health

Abstract: Due to late onset hypogonadism (LOH), there is an increased usage of testosterone replacement therapy (TRT) in the aging male population. Since prostate is a target organ for androgens and anti-androgenic strategies are used to treat and palliate benign prostate hyperplasia (BPH) and prostate cancer (PC), the prevalence of both increases with age, the possible influence of TRT on prostate health becomes highly relevant. The present review summarizes existing data on the associations between endogenous hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 160 publications
0
5
0
Order By: Relevance
“…These effects result in an increase in the number of cells and eventually lead to the development of BPH. 416 Changes in androgen levels and tissue remodeling caused by aging are generally considered to be the major determinants of BPH. There is clinical evidence that taking a 5α-reductase inhibitor can reduce the concentration of dihydrotestosterone in prostate tissue, thereby preventing the further development of BPH.…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%
“…These effects result in an increase in the number of cells and eventually lead to the development of BPH. 416 Changes in androgen levels and tissue remodeling caused by aging are generally considered to be the major determinants of BPH. There is clinical evidence that taking a 5α-reductase inhibitor can reduce the concentration of dihydrotestosterone in prostate tissue, thereby preventing the further development of BPH.…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%
“…Supraphysiological doses of androgens can increase muscle size and strength 23 . However, there is an increased risk of prostate enlargement and prostate cancer 24 . In summary, hormone replacement therapy is associated with significant side effects and its use in sarcopenia is limited.…”
Section: Current Treatments For Sarcopeniamentioning
confidence: 99%
“…It is transported to the target tissues in the body through binding of sex hormone binding globulin (SHBG) in the blood to function [15]. It is an important androgen that promotes human growth and development, and maintains normal organ function [16,17]. Obesity is a risk factor for OA, and studies have shown that testosterone de ciency can lead to obesity and insulin resistance, while testosterone therapy can inhibit fat deposition and reduce insulin resistance [18].…”
Section: Introductionmentioning
confidence: 99%